A vacuum-sealed miniature X-ray tube based on carbon nanotube field emitters - Heo, Sung Hwan (Springer, 2012)
A vacuum-sealed miniature X-ray tube based on a carbon nanotube field-emission electron source has been demonstrated. The diameter of the X-ray tube is 10 mm; the total length of the tube is 50 mm, and no external vacuum pump is required for the operation. The maximum tube voltage reaches up to 70 kV, and the X-ray tube generates intense X-rays with the air kerma strength of 108 Gy·cm(2) min(−1). In addition, X-rays produced from the miniature X-ray tube have a comparatively uniform spatial dose distribution.